An investigation of the profiles of bursts of solar radio noise - Wild, Peter Anthony Thornton (Rhodes University, Faculty of Science, Department of Physics, 1960)
[Summary] Chapter I . The general characteristics of solar radiation at metre wavelengths are described, with reference to data published in the literature. A brief description of some aspects of solar physics relevant to the study of solar noise is given, and the literature relating to the correlation of radio effects with solar disturbances is reviewed. Chapter II. A concise description of the apparatus constructed for the continuous recording of the flux density of solar radio noise at a frequency of 300 Mc/s is given, with some mention of difficulties experienced, and how these were overcome. Full circuit diagrams of electronic apparatus, and illustrative photographs, are supplied. Chapter III. The development of theories of the origin and propagation of solar noise radiation is historically reviewed and the success of each theory in explaining or predicting observed phenomena, is assessed. A working model is chosen from among these theories, and reasons for its adoption are given. Chapter IV. Observations made by the author of solar radiation at a frequency of 300 Mc/s are described, together with a description of the objects and methods, of analysis of the records. Chapter V. Phenomena observed by the author are compared with those observed by other workers. It is concluded that storm bursts are caused by transients similar to those producing Type II and Type ITI bursts, and a model for the production of storm bursts is tentatively suggested. Chapter VI. Suggestions for further research, including suggestions for methods of testing the author's conclusions, are made.
Keywords: Solar radio emission; Radio noise; Solar noise storms; Radio astronomy